Serotonin transporter (SERT) and translocator protein (TSPO) expression in the obese ob/ob mouse - Giannaccini, Gino (BioMed Central, 2011)
BACKGROUND: An ever growing body of evidences is emerging concerning metabolism hormones, neurotransmitters or stress-related biomarkers as effective modulators of eating behavior and body weight in mammals. The present study sought at examining the density and affinity of two proteins related to neurotransmission and cell metabolism, the serotonin transporter SERT and the cholesterol import-benzodiazepine site TSPO (translocator protein), in a rodent leptin-lacking mutant, the obese ob/ob mouse. Binding studies were thus carried out in brain or peripheral tissues, blood platelets (SERT) and kidneys (TSPO), of ob/ob and WT mice supplied with a standard diet, using the selective radiochemical ligands [(3)H]-paroxetine and [(3)H]-PK11195. RESULTS: We observed comparable SERT number or affinity in brain and platelets of ob/ob and WT mice, whilst a significantly higher [(3)H]-PK11195 density was reported in the brain of ob/ob animals. TSPO binding parameters were similar in the kidneys of all tested mice. By [(3)H]-PK11195 autoradiography of coronal hypothalamic-hippocampal sections, an increased TSPO signal was detected in the dentate gyrus (hippocampus) and choroids plexus of ob/ob mice, without appreciable changes in the cortex or hypothalamic-thalamic regions. CONCLUSIONS: These findings show that TSPO expression is up-regulated in cerebral regions of ob/ob leptin-deficient mice, suggesting a role of the translocator protein in leptin-dependent CNS trophism and metabolism. Unchanged SERT in mutant mice is discussed herein in the context of previous literature as the forerunner to a deeper biochemical investigation.